Validated educational technologies for health education for people with diabetes mellitus: integrative review (Research, Society and Development, 2022)
Objective: to identify scientific evidence about validated educational technologies for health education for people with diabetes mellitus. Method: This is an integrative literature review, carried out in March 2021, in the databases Latin American Literature in Health Sciences, Bibliographic Data in the Nursing Area of ​​Brazil, Medical Literature Analysis and System Online and SciVerse Scopus, using the descriptors educational technology, diabetes mellitus, nursing, validation, followed by the Boolean operator AND, without time frame, resulting in 14 selected studies, which were analyzed descriptively. Results: The literature points to the use of educational technologies as devices to assist health professionals in screening for diabetes mellitus, supporting health education actions, changing health behavior, improving self-care, self-management and care the needs of clinical practice. Conclusion: validation studies for health education are little explored when related to diabetes mellitus.